THE EFFECT OF PROVIDER EXCELLENT ON PROVIDER CONSUMER SATISFACTION OF PT. PELABUHAN INDONESIA (PERSERO) CONTAINER TERMINAL DEPARTMENT MAKASSAR - Tamara Aulia; Abd Rahman Kadir; M Sobarsyah (Digital Economy and Digital Transformation Review, 2023)
This studies goals to determine and examine how a lot affect the fine of carrier to the level of pride felt through customers who use the services of PT. Pelabuhan Indonesia IV (Persero) Branches Of Makassar box. The version used in this research are the technique of observation, interviews, questionnaires, and literature look at the use of a Linkert scale and method of determination of the pattern used turned into 93 samples. The technique of evaluation were used more than one linear regression techniques. The results showed that the fine of carrier which includes Realibility (X1), Responsiveness (X2), warranty (X3), Emphaty (X4), and Tangible (X5) collectively have a fine affect. Wherein the regression equation Y = 2,621 + 0,105 X1 + 0,182 X2 + 0,145 X3 +0,110 X4 + 0,373 X5 . In addition, the F test located that service fine has a large effect on customer pride with a importance level of 0.000 or 0%. but, primarily based on partial test (t), all variables have a large effect on customer pride with a large level for Realibility of 0,042 or 4.2%; warranty of 0,003 or 0,3%; Tangible of 0,000 or 0%; Emphaty 0,040 or 4.0% and Responsiveness of 0,017 or 1.7%.